Delayed H∞ switched control for uncertain nonlinear active suspension systems - Oncoy, Dante J.S. [UNESP]; Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C.M. [UNESP]; Faria, Flavio A. [UNESP]; Assunção, Edvaldo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
One of the most important topics in the automotive industry is the design of a suspension system that ensures better ride comfort and handling control. This paper presents design conditions for a H∞ controller that mitigates perturbations in dynamic response, and considering a time delay in the actuator. The nonlinear suspension system will be modeled as a Takagi-Sugeno (T-S) fuzzy system, and in order to obtain less conservatism in the design conditions, a Lyapunov-Krasovskii functional that depends of the membership functions (MFs) will be considered. The initial results present the design conditions of a parallel distributed compensation (PDC) controller. Therefore, the sprung and unsprung masses will be considered as uncertain nonlinear premise variables, which are not available for feedback, and a switched controller is proposed to deal with this problem. Simulation results are presented, demonstrating the effectiveness and improvement of the proposed strategy.
Keywords: Active suspension system; Memebership function dependent Lyapunov-Krasovskii functional; Parallel distributed compensation (PDC)